Development of Electronic Student Worksheets Problem Solving Oriented to Train Students' Critical Thinking Skills on Buffer Solutions - Eidelwais Joy Permata Yunika; Utiya Azizah (Asian Journal of Applied Education (AJAE), 2026)
The aims of this study are to train students' critical thinking abilities on buffer solution material by creating an E-Worksheet focused on problem-solving using the Canva tool. The method used was the Borg and Gall Research and Development (R&D) model up to the limited pilot test stage with students in grade XI at SMAN 22 Surabaya in the 2025/2026 academic year as subjects. According to the study's findings, the E-Worksheet has a mode of ≥4 and is valid in terms of both content and construct validity. The practicality of the E-Worksheet is demonstrated through student responses of 98.15% and observations of relevant activities ranging from 91.54% to 94.89%. Effectiveness was demonstrated through the N-gain test, in which 61.11% of students met the high criteria and 38.89% met the moderate criteria. The problem-solving-oriented E-Worksheet proven to be valid, practical, and effective in training students’ critical thinking skills.